METHODS OF TEACHING ENGLISH (Scientific journal of the Fergana State University, 2024)
This article delves into the various methods employed in teaching English and identifies the patterns that contribute to effective language learning. By exploring contemporary teaching strategies, such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), the flipped classroom model, and Content and Language Integrated Learning (CLIL), the study highlights their practical applications and impacts on student engagement and proficiency. The research includes a thorough review of academic literature, qualitative data from interviews and surveys, and observational and experimental studies. This comprehensive analysis aims to provide insights into the most effective pedagogical practices for English language instruction, offering educators a detailed understanding of how different methods can be integrated to address diverse learning needs and improve educational outcomes. The findings underscore the importance of adopting varied teaching strategies to foster a dynamic and successful language learning environment.